2005
DOI: 10.3171/foc.2005.19.5.10
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetics of meningiomas

Abstract: In this article the authors provide a brief description of the current understanding of meningioma genetics. Chromosome 22 abnormalities, especially in the Neurofibromatosis Type 2 (NF2) gene, have been associated with meningioma development. Loss of heterozygosity of chromosome 22 occurs in approximately 60% of meningiomas; however, loss of NF2 gene function occurs in only one third of these lesions. This discrepancy supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
1
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 87 publications
2
62
1
4
Order By: Relevance
“…More than 90% of grade III tumors exhibit aggressive behavior (local invasion and/or distant metastasis). 3) WHO grade I tumors almost never metastasize or invade adjacent structures. However, as this case demonstrates, a subset of WHO grade I meningiomas can have malignant potential.…”
Section: Discussionmentioning
confidence: 99%
“…More than 90% of grade III tumors exhibit aggressive behavior (local invasion and/or distant metastasis). 3) WHO grade I tumors almost never metastasize or invade adjacent structures. However, as this case demonstrates, a subset of WHO grade I meningiomas can have malignant potential.…”
Section: Discussionmentioning
confidence: 99%
“…68 This gene is found on chromosome 22q and encodes for a protein called merlin, whose main function is to link the cell membrane proteins to the cytoskeleton. Recent studies have revealed that merlin also plays a role as part of the actin cytoskeleton and is involved in the regulation of cell proliferation and growth and the initiation of neoplastic behavior.…”
Section: Genes Involved In Meningioma Tumorigenesismentioning
confidence: 99%
“…The etiology of meningiomas remains unclear, but ionizing radiation, brain injury, smoking, chronic viral infection, chromosomal abnormalities were proposed to be predisposing factors (Phillips et al, 2005). Meningiomas are generally benign and slow-growing tumors with less agressive behaviour (Ragel and Jensen, 2005). In this study the clinical, pathological characteristics and localizations of meningioma cases in our center at 2010-2012 have been analyzed.…”
Section: Introductionmentioning
confidence: 99%